Legal Pluralism: Concept, Theoretical Dialectics, and Its Existence in Indonesia - Achmad Hariri; Basuki Babussalam (Walisongo Law Review (Walrev), 2024)
Legal pluralism refers to the coexistence of multiple legal systems within a single society, encompassing state, customary, and religious laws. This concept is deeply rooted in Indonesia’s colonial legacy and cultural diversity, both of which have shaped the emergence of distinctive and layered legal practices. This study examines how legal pluralism operates within the Indonesian legal framework and the challenges involved in reconciling state law with non-state legal systems. It aims to analyze the forms and dimensions of legal pluralism in Indonesia, identify key obstacles to integrating these systems, and propose strategies to enhance justice and legal certainty. Employing a qualitative research approach with juridical and sociological perspectives, the study investigates the application of legal pluralism across various regions of Indonesia. The analysis highlights two main perspectives: juridical legal pluralism (the state’s formal recognition of customary law) and empirical legal pluralism (the lived reality of individuals subject to multiple normative orders). The findings reveal that legal pluralism reflects Indonesia’s socio-cultural complexity and offers opportunities for more inclusive governance. However, it also generates challenges, including legal uncertainty, overlapping authority, and unequal access to justice. The study concludes that a coordinated legal framework, which respects local traditions while upholding universal principles of justice, is essential for strengthening social cohesion and improving the effectiveness of Indonesia’s legal system. Pluralisme hukum merupakan kondisi di mana beberapa sistem hukum hidup berdampingan dalam satu masyarakat, meliputi hukum negara, hukum adat, dan hukum agama. Konsep ini berakar kuat pada warisan kolonial dan keragaman budaya Indonesia yang membentuk praktik hukum yang khas dan berlapis. Penelitian ini mengkaji bagaimana pluralisme hukum berfungsi dalam kerangka hukum Indonesia serta tantangan dalam menyelaraskan hukum negara dengan sistem hukum non-negara. Tujuan penelitian ini adalah untuk menganalisis bentuk dan dimensi pluralisme hukum di Indonesia, mengidentifikasi hambatan utama dalam integrasi antar sistem hukum, serta merumuskan strategi untuk memperkuat keadilan dan kepastian hukum. Dengan menggunakan metode penelitian kualitatif melalui pendekatan yuridis dan sosiologis, studi ini menelusuri penerapan pluralisme hukum di berbagai wilayah Indonesia. Analisis penelitian ini menyoroti dua perspektif utama: pluralisme hukum yuridis (pengakuan formal negara terhadap hukum adat) dan pluralisme hukum empiris (realitas individu yang tunduk pada berbagai sistem hukum). Hasil penelitian menunjukkan bahwa pluralisme hukum mencerminkan kompleksitas sosial-budaya Indonesia dan membuka peluang bagi tata kelola hukum yang lebih inklusif. Namun demikian, pluralisme ini juga menimbulkan tantangan seperti ketidakpastian hukum, tumpang tindih kewenangan, dan ketimpangan akses terhadap keadilan. Penelitian ini menyimpulkan bahwa diperlukan kerangka hukum yang terkoordinasi, yang menghormati tradisi lokal sekaligus menjunjung prinsip keadilan universal, guna memperkuat kohesi sosial dan meningkatkan efektivitas sistem hukum nasional. Keywords: Legal Pluralism; Customary Law; Legal Harmonization; Legal Certainty.